2007
DOI: 10.1080/00016340701444764
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue alterations in women with pelvic organ prolapse and urinary incontinence

Abstract: Our biochemical and morphological findings suggest a different organisation of collagen fibres in tissues of patients with USI+POP, when compared with both the controls and the POP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 28 publications
0
41
0
1
Order By: Relevance
“…[20][21][22] Several studies have compared the amount of total and individual subtypes of collagen in the supporting ligaments and vaginal tissue of women with POP to a control group (see Table 1). 19,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] Figure 1 Current anatomical considerations for prolapse. Level 1: The upper 1/3 of the vagina is suspended to the pelvic wall by the uterosacral and cardinal ligaments, condensations of endopelvic fascia.…”
Section: Collagen Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] Several studies have compared the amount of total and individual subtypes of collagen in the supporting ligaments and vaginal tissue of women with POP to a control group (see Table 1). 19,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] Figure 1 Current anatomical considerations for prolapse. Level 1: The upper 1/3 of the vagina is suspended to the pelvic wall by the uterosacral and cardinal ligaments, condensations of endopelvic fascia.…”
Section: Collagen Compositionmentioning
confidence: 99%
“…Two other studies found no difference in collagen content between women with prolapse and the control group. 24,25 These studies quantified collagen via hydroxyproline assay -hydroxyproline is a component of collagen and is thus an indirect measure of collagen levels. This assay is not collagen specific and is not entirely reliable in unpurified tissue samples, with results differing depending on assessment methods.…”
Section: Studies Of Collagen Composition In Uterosacral/ Cardinal Ligmentioning
confidence: 99%
“…Так, опущение передней стенки влагалища со-провождается утратой поддерживающей функ-ции уретры, что обусловливает гипермобиль-ность шейки мочевого пузыря и, как следствие, развитие СНМ. В многочисленных исследовани-ях приводятся данные о разнообразных струк-турно-метаболических нарушениях соединитель-нотканных образований малого таза у женщин с расстройствами мочеиспускания [10,17,19]. Согласно интегральной концепции, ключевое значение в альтерации соединительной ткани при СНМ у женщин принадлежит нарушениям метаболизма коллагена, эластина и трансформи-рующего фактора роста β [7].…”
unclassified
“…The role of the connective tissue component is to counteract both stretch and compression of the pelvic floor exerted by the gravitational and inertial forces of the intra-abdominal pressure and to repair damaged tissues (2,4,6). This supportive function is determined by the tensile strength of collagen in the extracellular matrix that is maintained by continuous remodelling of collagen (1,3).…”
Section: Introductionmentioning
confidence: 99%
“…Support-related pelvic floor dysfunctions including pelvic organ prolapse (POP), stress urinary incontinence (SUI) and faecal incontinence are caused by structural defects in the complex supportive apparatus formed by the connective tissue and striated muscles of the pelvic floor (1)(2)(3)(4)(5)(6)(7). The role of the connective tissue component is to counteract both stretch and compression of the pelvic floor exerted by the gravitational and inertial forces of the intra-abdominal pressure and to repair damaged tissues (2,4,6).…”
Section: Introductionmentioning
confidence: 99%